The Effect of Market Orientation and Strategic Flexibility on Competitive Advantage through Hotel Firm Performance in Surabaya - Wisesa , Gabriella; Ellitan, Lena (Journal of Entrepreneurship & Business, 2025)
Purpose: The hospitality and tourism industry is a vital sector in Indonesia, significantly contributing to the country's economy. East Java is the province with the second-largest number of hotel buildings in all of Indonesia. The largest hotel star category in both Indonesia and East Java, particularly in Surabaya, the capital of East Java, is a three-star hotel. The tight competition in the hospitality industry, especially among the hotels themselves, makes business actors in this industry need to think about ways to survive. A key factor that enables a company to survive in a highly competitive industry is a competitive advantage. This study aims to investigate the impact of market orientation and strategic flexibility on a firm's competitive advantage, as measured by its performance. The study was conducted on three-, four-, and five-star hotels in Surabaya. Method: Research data were obtained through the distribution of questionnaires to owners or managers of three-, four-, and five-star hotels in Surabaya. A total of 110 responses were used as research data and processed using SEM-PLS data processing techniques. Result: The study's results showed that the market orientation variable had an impact on strategic flexibility and competitive advantage, but did not affect firm performance. The strategic flexibility variable was found to affect firm performance and competitive advantage. Firm performance was also found to have a significant effect on competitive advantage.